Analisis Implementasi Kebijakan Program Penanggulangan Stunting di Dinas Kesehatan Kabupaten Enrekang - Syahruddin, Mega; Fachrin, Suharni A.; Samsualam, Samsualam (Mandalika Institute, 2024)
This study aims to analyze the implementation of the stunting prevention program policy conducted by the Enrekang District Health Office. Stunting is a serious public health issue in Indonesia, including in Enrekang District. The implementation of this policy involves various stakeholders such as local government, community health centers, and community organizations. The research method used is a qualitative approach. Data were collected through in-depth interviews with health workers and related stakeholders. The results show that the implementation of the stunting prevention program policy at the Enrekang District Health Office has faced various challenges and achieved some successes. Key factors influencing the success of implementation include well-trained human resources, inter-organizational coordination, accessibility of health services, and community participation. This study also identifies several recommendations to enhance program effectiveness, including strengthening HR capacity, improving access to and quality of health services, more intensive educational campaigns, and expanding collaboration among organizations. This research provides in-depth insights into the implementation of the stunting prevention program policy in Enrekang District and contributes to the development of strategies to address stunting issues at the local level.